Cancer stem cells and their niche in cancer progression and therapy - Liu, Qiuping; Guo, Zongliang; Li, Guoyin; Zhang, Yunxia; Liu, Xiaomeng; Li, Bing; Wang, Jinping; Li, Xiaoyan (Cancer cell international, 2023)
High recurrence and metastasis rates and poor prognoses are the major challenges of current cancer therapy. Mounting evidence suggests that cancer stem cells (CSCs) play an important role in cancer development, chemoradiotherapy resistance, recurrence, and metastasis. Therefore, targeted CSC therapy has become a new strategy for solving the problems of cancer metastasis and recurrence. Since the properties of CSCs are regulated by the specific tumour microenvironment, the so-called CSC niche, which targets crosstalk between CSCs and their niches, is vital in our pursuit of new therapeutic opportunities to prevent cancer from recurring. In this review, we aim to highlight the factors within the CSC niche that have important roles in regulating CSC properties, including the extracellular matrix (ECM), stromal cells (e.g., associated macrophages (TAMs), cancer-associated fibroblasts (CAFs), and mesenchymal stem cells (MSCs)), and physiological changes (e.g., inflammation, hypoxia, and angiogenesis). We also discuss recent progress regarding therapies targeting CSCs and their niche to elucidate developments of more effective therapeutic strategies to eliminate cancer.